2020
DOI: 10.31234/osf.io/pw86b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing the Future: An Initial Test of Future Specificity Training (FeST)

Abstract: A range of psychiatric disorders are characterised by impairments in episodic future thinking (EFT), and particularly simulating specific, spatiotemporally-located future events. To date, no study has examined whether training can lead to sustained improvement in the specificity of EFT. In this study, participants (N=60; M age=31, SD=13.2) were randomized to a two-session, group-based program on future thinking (Future Specificity Training; FeST) or wait-list. At follow-up the training group, relative to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Given the highly focused nature of the training, perhaps this is unsurprising. The lack of effect on future specificity also suggests that although these two thought processes overlap substantially, focused training may be needed in order to see improvements, for example with recent Future Thinking Specificity Training (FeST; Hallford, Yeow, et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
“…Given the highly focused nature of the training, perhaps this is unsurprising. The lack of effect on future specificity also suggests that although these two thought processes overlap substantially, focused training may be needed in order to see improvements, for example with recent Future Thinking Specificity Training (FeST; Hallford, Yeow, et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
“…They were supervised by the first author, a registered clinical psychologist. The training was adapted for use in a clinical depression population from the previous manualised version used in a community sample (Hallford, Yeow, et al, 2020). Both manuals are open access and available online (https://osf.io/mq6y3/).…”
Section: Future Event Specificity Training (Fest)mentioning
confidence: 99%
“…Anticipatory and anticipated pleasure were assessed as distinct constructs given their conceptual differences (Baumgartner et al, 2008) and empirical distinction in their associations with behavioural intentions and phenomenological characteristics of EFT (Barsics et al, 2016;Baumgartner et al, 2008). The items were taken from previous studies examining prospective emotions in clinical (Hallford, Barry, et al, 2020;Hallford, Sharma, et al, 2020) and non-clinical samples (Hallford, Yeow, et al, 2020) where they have demonstrated convergent, divergent, and construct validity.…”
Section: Anhedonia-related Variablesmentioning
confidence: 99%
See 2 more Smart Citations